The spreading of the non-native caprellid (Crustacea: Amphipoda) Caprella scaura Templeton, 1836 into southern Europe and northern Africa: a complicated taxonomic history. - ROS CLEMENTE, M. (Mediterranean Marine Science, 2013)
Caprella scaura, originally described by Templeton (1836) from Mauritius and later reported as several subspecies from numerous areas of the world, was found for the first time in the Mediterranean in 1994. Since this report, the species was found in several Mediterranean locations. To explore the current distribution of C. scaura in the Iberian Peninsula and adjacent areas, we surveyed marine fouling communities from 88 marinas along the whole Iberian Peninsula and North Africa, 3 from Italy, 1 from France, 1 from Malta and 1 from Greece between June 2011 and June 2012. The results of this survey report the first confirmed record of C. scaura in Corsica (France), Creta (Greece) and Morocco, and confirm an extensive distribution of C. scaura along the Spanish Mediterranean coast and the Strait of Gibraltar. The species was absent in the north Atlantic coast of Spain and the upper distribution limit in the eastern Atlantic coast is the locality of Cascais, in the south coast of Portugal. All populations studied belong to the same morphological form, with match with the subspecies C. scaura typica from Brazil and C. scaura scaura from Mauritius, suggesting that these two subspecies could correspond to the same “variety”.